UTILIZATION OF DIGITAL MEDIA IN MATHEMATICS LEARNING IN PUBLIC ELEMENTARY SCHOOLS IN BANDUNG - zatman, Zatman Payung; Yaya Sukjaya Kusumah; Endang Cahya Mulyaning; Bambang Avip (Jurnal Tunas Pendidikan, 2025)
This study aims to analyze the use of digital media in mathematics learning in public elementary schools in the city of Bandung. This study uses a descriptive quantitative research design. The study population consisted of teachers and students from public elementary schools in the city of Bandung, with a randomly selected sample from 20 public elementary schools and each school was taken with 5 teachers and 6 students. The instruments used were observations, questionnaires, and documentation to collect data, which included the perception of teachers and students on the use of digital media in mathematics learning. The types of data taken include respondent scores from questionnaires, observation results and documentation which are then analyzed using descriptive statistics to obtain the average score and interpretation. The results showed that teachers actively utilize various digital media in mathematics learning, such as learning videos and educational applications, which contributed to increased student interest and engagement. In addition, students responded positively to the use of digital media, with 84% stating that learning became more engaging and enjoyable. The research also identified major obstacles, such as unstable internet access and device limitations for students. The research concludes that the use of digital media in mathematics learning in primary school can increase students' interest and engagement, as well as help in understanding abstract concepts.